The Biology of Alcoholism 1971
DOI: 10.1007/978-1-4615-6525-3_17
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Alcoholic Beverages

Abstract: HISTORYHundreds of thousands of years ago, people presumably became aware that a strange metamorphosis occurred when honey, fruits, berries, cereals and other plant materials were mixed with water and left in the warmth of the sun. The products made from fermented honey were the first meads (perhaps the earliest alcoholic beverages known to human beings; Gayre, 1948), those

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Alcohol was administered at a dose of 0.5 g/kg of body weight, mixed with orange juice (total amount=400 ml). Vodka (37.5% alcohol) was chosen because of its purity compared with other alcohol-containing beverages (Leake and Silverman 1971). The placebo drink was the same total volume of orange juice (400 ml), so that the visual appearance was quite similar between alcohol and placebo drinks.…”
Section: Subjectsmentioning
confidence: 99%
“…Alcohol was administered at a dose of 0.5 g/kg of body weight, mixed with orange juice (total amount=400 ml). Vodka (37.5% alcohol) was chosen because of its purity compared with other alcohol-containing beverages (Leake and Silverman 1971). The placebo drink was the same total volume of orange juice (400 ml), so that the visual appearance was quite similar between alcohol and placebo drinks.…”
Section: Subjectsmentioning
confidence: 99%
“…After breakfast their weight was measured, and they were served alcohol in doses of 1 g/kg of body weight, mixed with orange juice (75% of total volume). Vodka (40% alcohol) was chosen because of its purity compared with other alcohol-containing beverages (Leake & Silverman, 1971). The first rCBF measurement started 15 min after drinking was completed and the subjects had rinsed their mouths thoroughly with water.…”
Section: Subjectsmentioning
confidence: 99%
“…Furthermore, in each beverage class, a beverage with a high content of congeners would contain more parts per million (ppm) of the various congeners, such as esters, the higher alcohols, aldehydes, methanol, and tannins. For example, Leake and Silverman (1971) reported that dry vermouth contained 388 ppm of higher alcohols; a red wine, such as Burgundy, 298 ppm; Scotch, 808 ppm; and gin, 13 ppm. If the congeners (e.g., higher alcohols) in a beverage CS contribute taste and aroma characteristics that share stimulus characteristics with ethanol, then ethanol may not be a separable conditioning element in that beverage CS.…”
Section: Discussionmentioning
confidence: 99%
“…Leake & Silverman's, 1971, use of the term congeners). Since ethyl alcohol (ethanol) is in all alcoholic beverages, it seems important to know whether or not ethanol provides a functional stimulus for conditioning in the beverage compound conditioned stimulus (CS).…”
Section: Virginia Polytechnic Institute and State University Blacksbmentioning
confidence: 99%